An Unexpected Finding in a Child with Scarlet Fever: Hepatitis - Kocamaz, H.; Isikay, S.; Demiroren, K.; Dogan, Y. (Univ West Indies Faculty Medical Sciences, 2021)
Hepatitis would be related to non-hepatotropic virus. A 6-year-old boy was presented with acute hepatitis finding. He had specific rashes for scarlet fever. His liver was enlarged and liver enzyme was elevated. Other reasons of acute viral hepatitis were excluded. Liver enzymes were normalized after appropriate antibotherapy. We aimed to remind unusual presentation of scarlet fever and uncommon reasons of acute hepatitis.
Keywords: Antibotherapy; child; hepatitis; scarlet fever